Influences of carbon nanofillers on mechanical performance of epoxy resin polymer - Singh S.; Srivastava V.K.; Prakash R. (My University, 2025)
The influence of multi-walled carbon nanotubes (MWCNTs) and graphene nanoplatelets (GnPs) on epoxy resin was investigated to compare their mechanical properties. MWCNT/epoxy resin and GnP/epoxy resin composites were compared with each other for their tensile strength, compressive strength, Charpy Impact and Izod impact energy with the variation of weight percentage ratio of nanofiller ranging from 0.5, 1.0, 2.0 and 3.0, respectively. The result shows that GnP/epoxy resin composite gave better tensile and compressive strength compared to MWCNT/epoxy resin composite whereas Izod impact energy, Charpy impact energy and dynamic fracture toughness of MWCNT/epoxy resin composite resulted in better impact resistance than the GnP/epoxy resin composite. Thermal stability and microstructural properties of composites were measured using Thermogravimetric analysis (TGA), transmission electron microscope (TEM) and scanning electron microscope (SEM). © 2014, The Author(s).